Construction of Nanomaterials and the Role of Rutin in the Treatment of Cerebral Hemorrhage - Xin Li; Zhenzhong Gao (Advances in Materials Science and Engineering)
Cerebral hemorrhage generally refers to nontraumatic cerebral parenchymal hemorrhage. In China, about 20%–30% of all stroke in a month after the mortality rate can be as high as 40%. And most of the survivors have obvious neurological dysfunction, to the patient’s family and society from all walks of life caused great psychological pressure, which will seriously affect the human physical and mental health. This article aims at studying the construction of nanomaterials and the role of rutin in the treatment of ICH. It first introduces the characteristics of nanomaterials; nanomaterials have some special effects based on their special internal structural properties and surface states. These effects derive many physical and chemical properties that general substances do not possess, such as optical, electrical, magnetic, catalytic, and photocatalytic properties. A simple analysis of cerebral hemorrhage then gives the nanomaterials the first-principles algorithm. Practical application of nanomaterials is a class of nanomaterials, which have many strange chemical characteristics such as special light, electric, magnetic, thermal, mechanical, mechanical physical, and chemical characteristics. Then, the nanocomposite of rutin electrochemical detection is analyzed, and finally rutin and analog brain drug dynamics is discussed. The experimental results showed that the RSD of samples at room temperature, freeze-thaw cycles, and long-term stability of the mice were less than 5.0%, and the stability of mouse brain tissue homogenate samples completely meets the requirements of troxerutin, rutin, and troxerutin aglycone.